ADVERSITY QUOTIENT QUITTERS PADA KARYAWAN GENERASI Z DI PT GRAMEDIA ASRI MEDIA YOGYAKARTA - Naufal Ade Darmansyah; Reny Yuniasanti (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
This study explores the characteristics and challenges faced by Generation Z (born 1996-2010) in the workplace, specifically at PT Gramedia Asri Media Yogyakarta. Generation Z, currently aged 15-26, demonstrates a need to gather experience through various positions and prefers collaboration and innovation within a professional environment. This research is a qualitative phenomenological study aimed at identifying the presence of adversity quotient among Generation Z employees at PT Gramedia Asri Media Pakuwon Mall Yogyakarta. The participants consist of three individuals who are employees of Gramedia Pakuwon Mall, as well as three significant others who serve as their supervisors. Data collection was conducted through in-depth interviews with semi-structured questions carried out face-to-face. The results indicate that all three participants possess equal levels of control, recognition, achievement, and endurance in facing workplace situations. Despite encountering complex issues, Participants D, A, and L were able to effectively overcome these challenges, thereby resolving problems and reducing their desire to leave their jobs.